2018
DOI: 10.12965/jer.1836420.210
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of gabapentin and exercises in the treatment of carpal tunnel syndrome: a randomized clinical trial

Abstract: Carpal tunnel syndrome (CTS) is one of the reasons for labor abandonment due to inability and pain. The aim of this study was to evaluate the effectiveness of gabapentin and exercise training in the treatment of CTS and compare their effects. This single-blind clinical trial was conducted on patients referred to the Imam Hossein hospital’s electrodiagnostic (EDX) unit. The patients randomly assigned into four groups: using nocturnal splint as an approved treatment in the control group; taking 300-mg gabapentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This difference could be related to the diversity in intervention methods, some acupuncture sessions and the primary characteristics of patients. In Hessami et al study showed that the use of splint alone in mild CTS is a suitable and adequate treatment; however, in moderate CTS, taking gabapentin along with splinting and exercise indicated better treatment results compared to splinting alone (49). The current study found that nerve and tendon gliding exercises can improve grip and pinch strength which is consistent with Pinar et al results (23).…”
Section: Discussionsupporting
confidence: 87%
“…This difference could be related to the diversity in intervention methods, some acupuncture sessions and the primary characteristics of patients. In Hessami et al study showed that the use of splint alone in mild CTS is a suitable and adequate treatment; however, in moderate CTS, taking gabapentin along with splinting and exercise indicated better treatment results compared to splinting alone (49). The current study found that nerve and tendon gliding exercises can improve grip and pinch strength which is consistent with Pinar et al results (23).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, several clinical trials have suggested the efficacy of GABA use for off-label pain conditions (e.g. chronic sciatica; irritable bowel syndrome) and for reducing acute and chronic postoperative pain and OPI use [50][51][52][53][54][55]. However, given the safety concerns about GABAs, there have been calls for placing more stringent regulations on gabapentin at the federal level and to include gabapentin monitoring in state prescription drug monitoring programs (PDMPs) to promote safety.…”
Section: Discussionmentioning
confidence: 99%
“…Hesami et al researched a study in 2018 on the treatment of carpal tunnel syndrome and gabapentin [ 40 ]. The cases were divided into four groups with different combinations of nocturnal splint, exercise and gabapentin.…”
Section: Discussionmentioning
confidence: 99%